Simplify both sides of the equation
-5/2 x +3/4 x = -3/4
Combine like terms
(-5/2 x + 3/4 x )
-7/4 x = -3/4
-7/4 x = -3/4
Multiply both sides by 4/(-7)
(4/-7)*(-7/4 x ) = (4/-7 ) * ( -3/4 )
x = 3/7
Answer:
3 pound cake=48 ounces)4 pound cake=64 ounces
Step-by-step explanation:
[16 ounces = 1 pound]-so you got this
James bought a cake that weighed over 4 pounds.
And one that is 3 pounds,so you wanna multiply 16 x 3 and you get 48
So that leaves the 3 pound cake to be 48 ounces
Just like the first one,you wanna multiply 16 x 4 and you get 64
Equation 1 ==> y = -4x + 2
Equation 2 ==> y = x - 3
Substitude equation 2 into 1
x - 3 = -4x + 2
-5 = -5x
x = 1
Substitude x into equation 2
y = 1 - 3
y = -2
Coordinates is (1, -2)
Answer is D.
The LCD = 6x^2y^3 ( because LCD of 3 and 6 = 6, LCD of x^2 and x = x^2 and LCD of y and y^3 = y^3)
now divide 3x^2y into the LCD then multiply this by 5 to get the first term in the numerator and do similar process to get second term, so we get:-
5(2y^2) - 4(x)
------------------
6x^2y^3
= 2( 5y^2 - 2x)
-----------------
6x^2y^3
= 5y^2 - 2x
-----------
3x^2y^3
f(x) means the function of x
so the function is the input is x and the output is f(x), read "f of x". The output f(x) is sometimes given an additional name y by y = f(x). The example that comes to mind is the square root function on your calculator.